FAKTOR-FAKTOR YANG MEMPENGARUHI PENAMBAHAN BERAT BADAN BAYI - Widyarini, Ika Maulidia; Yuliani, Ita; Suprapti, Suprapti (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2024)
Weight gain in babies is part of monitoring which influences various factors, namely genetics, gender, breastfeeding patterns, exclusive breastfeeding, supplementary feeding, family socio-economic status, and baby massage stimulation. The proportion of recorded growth monitoring in the last 12 months in children age 0-59 months in Indonesia was 43,3% and 56,9% in East Java. And the figures below regarding exclusive breastfeeding in 2022 have decreased from 2021 by 0,3%. This study aims to identify factors that influence infant weight gain. The method used is a literature review with a traditional literature review type obtained from 2 databases, namely Google Scholar and PubMed using inclusion and exclusion criteria. The literatures used were published from 2018-2022. Keywords used in the literature search: “Infants”, “Infant Weight Gain”,